2012
DOI: 10.1007/978-3-642-34109-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Suffix Trees for Repetitive Texts

Abstract: Abstract. We design a new compressed suffix tree specifically tailored to highly repetitive text collections. This is particularly useful for sequence analysis on large collections of genomes of the close species. We build on an existing compressed suffix tree that applies statistical compression, and modify it so that it works on the grammar-compressed version of the longest common prefix array, whose differential version inherits much of the repetitiveness of the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, GCT uses much less space on repetitive collections, around 2-3 bpc. This is slightly larger than the previous structure for repetitive collections [2,1] but one to two orders of magnitude faster than it. On an extremely repetitive collection, GCT uses even less space than that previous structure, near 0.5 bpc.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…However, GCT uses much less space on repetitive collections, around 2-3 bpc. This is slightly larger than the previous structure for repetitive collections [2,1] but one to two orders of magnitude faster than it. On an extremely repetitive collection, GCT uses even less space than that previous structure, near 0.5 bpc.…”
Section: Introductionmentioning
confidence: 69%
“…Fischer et al [12] proved that H was in addition compressible when the text was statistically compressible, but Cánovas and Navarro [7,1] found out that the compressibility was not significant on standard texts. Instead, Abeliuk and Navarro [2,1] showed that the technique proposed to compress H [12] made a significant difference on repetitive texts.…”
Section: Compressed Suffix Treesmentioning
confidence: 99%
See 3 more Smart Citations